Salt in his shoes : Michael Jordan in pursuit of a dream - Jordan, Deloris; Jordan, Roslyn; Nelson, Kadir (New York : Aladdin Paperbacks, 2003)
A young Michael Jordan puts salt in his shoes, hoping it will help him grow tall enough to become a famous basketball player.
Booklist
School Library Journal
Wilson's Children
Booklist, February 2001
Bulletin (Center for Children's books), December 2000
Kirkus Review, December 2000
Keywords: Jordan, Michael, -- 1963- -- Juvenile fiction; Jordan, Michael, -- 1963- -- Fiction; Jordan, Michael, -- 1963- -- Fiction; Basketball -- Juvenile fiction; Stature -- Juvenile fiction; Basketball -- Fiction; Size -- Fiction; Basketball -- Fiction; Size -- Fiction